Paris is burning [videorecording (DVD)] - Livingston, Jennie; Livingston, Jennie; Corey, Dorian, 1937-1993; LaBeija, Pepper, 1950-2003; Ninja, Willi (Criterion Collection, 2020)
Reveals New York City's community of minority drag queens where competitive balls and fashion are the source of pride and self-affirmation.